Conservation Opportunities Arise From the Co-Occurrence of Surfing and Key Biodiversity Areas - Reineman, Dan R.; Koenig, Kellee; Strong-Cvetich, Nik; Kittinger, John N. (Frontiers in Marine Science, 2021)
Conserving biodiversity and ecosystem services requires diverse models that empower communities to steward and benefit from resources. Here we investigate the potential of surfing resources, a new conservation asset class, and the surfing community, an underutilized conservation constituency, to conserve marine biodiversity. We conducted a spatial analysis of the overlap among Key Biodiversity Areas, Marine Protected Areas (MPAs), and 3,755 surf breaks globally. We find that 62.77% of surf breaks are not within MPAs and that 25.81% of all surf breaks are within 5 km of a Key Biodiversity Area, but are not within a MPA, suggesting that strategic conservation opportunities arise from the co-occurrence of surfing resources and biodiversity priorities. Establishing or extending protections to surfing ecosystems could increase protection for biodiversity at one-quarter of surf breaks. Sustainable management of these resources ensures their ability to provide for the character, economy, and development of coastal communities worldwide.